ANALISIS SEGMENTASI SUPLEMEN MULTIVITAMIN BERDASARKAN GAYA HIDUP AIO (ACTIVITIES, INTEREST AND OPINION) DI KOTA PEKANBARU - Adrianof Agustino; Sri Restuti; Henny Noviasari (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The research was conducted in Pekanbaru in order to determine and analyze the segmentation of lifestyle AIO (Activities, Interest and Opinion) multivitamin supplement consumers.In this research conducted by taking the 135 respondents with minimum age of 17 years who live in Pekanbaru and has been using a multivitamin supplement at least one month. In this study using lifestyle variables AIO (Activities, Interest and opinion) and use the method of cluster analysis using SPSS Version 16. Based on the analysis formed three groups: group1, Body Fit (17.03%) with characteristic dominant in social activities, vacation, shopping, recreation intrest and opinion of education. Group2, Keep Fresh (15.56%) has a characteristic an interest of food and challenges of the job. And group3, Need Energy (67.41%) which has the characteristics of the activities to entertain themselves and the club membership has a high valuation, interest in the community, a sense of familiarity and have interest great success and this group also has an opinion to entrepreneurship and consideration of the product is higher than the other groups. The results of this research can help increase sales by making the right marketing strategy and adapted to the characteristics of each group that has been formed.Keywords: Segmentation, Lifestyle AIO, Cluster Analysis